2017
DOI: 10.1163/15685403-00003687
|View full text |Cite
|
Sign up to set email alerts
|

Temporal distribution of crustaceans in forested freshwater wetlands: responses to changes in the hydroperiod

Abstract: Studies on crustacean communities in Chilean wetlands are scarce. The aim of this study was to characterize the crustacean community in forested wetlands from southern Chile and to establish their relation with the variations in the hydrological regime. In total, 540 samples were taken using three complementary sampling techniques in five wetlands during 2011 and 2012. The results show a total of four species of crustaceans, of which the amphipod Hyalella patagonica (Cunningham, 1871) (Hyalellidae) was dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
1
0
1
Order By: Relevance
“…During the rainy season (June-August), they come to the surface or to shallow zones, and aft er the end of the rainy season, in spring, summer and autumn, individuals are hidden in deep zones of their galleries (Rudolph, 2013 a, b). Th e associated communities of the habitats are poorly studied, with the exception of native forest wetlands at 38° S, where crustaceans such as amphipod Hyalella patagonica (Cunningham, 1871), isopod Heterias exul (Mueller 1892) and decapod Aegla araucaniensis (Jara, 1980) (Correa-Araneda et al, 2017) with high aquatic insect diversity (Correa-Araneda et al, 2021) were reported as associated fauna, which would be similar to the fi rst descriptions of fl ooded plains at the same latitude ( De los Rios Escalante et al, 2021).…”
Section: Introductionsupporting
confidence: 58%
“…During the rainy season (June-August), they come to the surface or to shallow zones, and aft er the end of the rainy season, in spring, summer and autumn, individuals are hidden in deep zones of their galleries (Rudolph, 2013 a, b). Th e associated communities of the habitats are poorly studied, with the exception of native forest wetlands at 38° S, where crustaceans such as amphipod Hyalella patagonica (Cunningham, 1871), isopod Heterias exul (Mueller 1892) and decapod Aegla araucaniensis (Jara, 1980) (Correa-Araneda et al, 2017) with high aquatic insect diversity (Correa-Araneda et al, 2021) were reported as associated fauna, which would be similar to the fi rst descriptions of fl ooded plains at the same latitude ( De los Rios Escalante et al, 2021).…”
Section: Introductionsupporting
confidence: 58%
“…In this context, in northern Chilean Patagonia (38-42° S), there are many protected areas with native perennial forest with many kind of unpolluted water bodies such as wetlands, streams and small lakes associated, that are poorly studied in their aquatic fauna (Correa-Araneda et al, 2017). Also, other important risk for invertebrate native species conservation is the presence of introduced salmonids that are very invasive species that has a strong predator against native benthic fauna, specifi cally insects and crustaceans (Soto et al, 2006(Soto et al, , 2007Encina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…* email: j.riquelme14@ufromail.cl Las aguas continentales de la Patagonia chilena, específicamente de la región de la Araucanía (38° S), por su marcado endemismo, principalmente en ecosistemas con baja intervención antrópica como zonas asociadas a bosques nativos siempre verdes (Correa-Araneda et al, 2017), como por ejemplo zonas altas de ríos donde hay baja intervención antrópica asociados a bosques nativos . La presente nota tiene como objetivo hacer un reporte sobre la presencia de crustáceos en el arroyo localizado en el predio protegido de Rucamanque, que corresponde a una zona relicto de bosque nativo propiedad de la Universidad de la Frontera.…”
unclassified